From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Minute‐Scale Adsorption of Diverse Marine Viruses Onto Clay Minerals - Lanlan Cai; Yuan Tian; Xuan Qiu; Yongle Xu; Hailiang Dong; Rui Zhang (Environmental Microbiology, 2026)
Viruses are ubiquitous biological entities with important roles in microbial mortality, genetic exchange and biogeochemical cycles. Clays, the most abundant mineral constituents on Earth, function as highly effective adsorbents for viruses, critically modulating their environmental persistence and ecological impact. However, the mechanisms and environmental drivers governing virus–clay interactions remain poorly understood. This study systematically investigates the adsorption kinetics of nine marine viruses onto a clay mineral (smectite, NAu‐2) under environmentally representative conditions. Viruses isolated from distinct hosts (heterotrophic bacteria, cyanobacteria and eukaryotic algae) and exhibiting diverse morphological features (myovirus, siphovirus, podovirus and tailless virus) were evaluated across gradients of NAu‐2/virus concentrations, pH, temperature and ionic strength. Elevated NAu‐2 concentrations (> 50 mg/L) induced rapid and near‐complete virus adsorption (90%–99%) within 1 min, while low concentrations (0.1–10 mg/L) yielded efficiencies from negligible to > 50%. Adsorption dynamics showed minimal correlation with viral morphology and instead depended on physicochemical properties. Electron microscopy revealed preferential viral localization at edge sites of NAu‐2, driven by charge heterogeneity from protonated alumina‐oxygen octahedra. These findings provide quantitative information on virus–clay interactions and offer key insights into the availability, transport and fate of viruses in the environment, paving the way for more accurate parameterization of biogeochemical cycling across ecosystems.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Does Water Rights Reform Reduce Water Usage for Agriculture? Evidence From City‐Level Panel Data in China - Hang Xu; Rui Yang (Irrigation and Drainage, 2025)
Existing policies promoting agricultural water conservation focus mainly on promoting water‐saving irrigation through subsidy policies, but this approach leads to a rebound effect, making obtaining the desired water‐saving result challenging. Moreover, many countries have begun to realize that the market‐oriented allocation of water resources through water rights reform (WRR) may be a more effective way of managing water resources to achieve agricultural water conservation. On the basis of the WRR pilot policy in China, this paper uses an empirical difference‐in‐differences (DID) strategy to analyse whether the WRR can reduce agricultural water use. The empirical results show that the WRR can reduce water use by 7% on average, and this result still holds after contemporaneous policies and alternative outcome measures are considered. The possible mechanism is that the WRR has changed the planting structure for food crops and cash‐crops and promoted water resource transfer from the agricultural sector to the non‐agricultural sector. The heterogeneity analysis indicates that the water‐saving effect of WRR is worse in areas with higher land potential or with better economic conditions. Therefore, the promotion of the WRR needs to consider agricultural production conditions and the economic situation.

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Morphology, phylogeny, and polyurethane degrading ability of Lasiodiplodia iraniensis and Mortierella alpina - Rui-Fang Xu; Saowaluck Tibpromma; Samantha C. Karunarathna; Kevin D. Hyde; Chayanard Phukhamsakda; Eyalira J. Okal; Dong-Qin Dai; Ekachai Chukeatirote; Sehroon Khan; Abdallah M. Elgorban; Peter E. Mortimer (New Zealand Journal of Botany, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Salinity as a key factor affecting viral activity and life strategies in alpine lakes - Lin Zang; Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Xuanying Song; Yunlan Yang; Lanlan Cai; Keshao Liu; Guannan Mao; Mukan Ji; Rui Zhang (Limnology and Oceanography, 2024)
Viruses are major players in the biosphere, yet little is known about their dynamics and life strategies in alpine lakes, particularly those on the Tibetan Plateau. We investigated microbial abundance, viral dynamics, and viral life strategies in 10 high‐altitude Tibetan lakes and found that they harbor high levels of active viruses. Salinity was identified as a crucial factor influencing viral abundance, dynamics, as well as viral life strategies. Lytic and lysogenic viral productions in moderate‐ and high‐salinity lakes were significantly higher than those in freshwater lakes. A trade‐off between viral life strategies resulted in a switch from lysis to lysogeny in high‐salinity lakes. Virus‐mediated cell lysis and virus decay in sampled Tibetan lakes could release about 162.72 and 2.84 μ g C L −1 d −1 , respectively. These findings revealed the crucial role of viruses in the carbon cycle of Tibetan lakes, and a switch in viral life strategies may impact their contribution to the carbon cycle. The potential impact of salinity changes triggered by climate change on the carbon cycle in alpine lakes worldwide is highlighted.

Phylogenetic distance–decay patterns are not explained by local community assembly processes in freshwater lake microbial communities - Yian Gu; Zhidan Li; Peng Lei; Rui Wang; Hong Xu; Ville‐Petri Friman (Environmental Microbiology, 2023)
While water and sediment microbial communities exhibit pronounced spatio‐temporal patterns in freshwater lakes, the underlying drivers are yet poorly understood. Here, we evaluated the importance of spatial and temporal variation in abiotic environmental factors for bacterial and microeukaryotic community assembly and distance–decay relationships in water and sediment niches in Hongze Lake. By sampling across the whole lake during both Autumn and Spring sampling time points, we show that only bacterial sediment communities were governed by deterministic community assembly processes due to abiotic environmental drivers. Nevertheless, consistent distance–decay relationships were found with both bacterial and microeukaryotic communities, which were relatively stable with both sampling time points. Our results suggest that spatio‐temporal variation in environmental factors was important in explaining mainly bacterial community assembly in the sediment, possibly due lesser disturbance. However, clear distance–decay patterns emerged also when the community assembly was stochastic. Together, these results suggest that abiotic environmental factors do not clearly drive the spatial structuring of lake microbial communities, highlighting the need to understand the role of other potential drivers, such as spatial heterogeneity and biotic species interactions.

Do not ignore the effects of phosphorus and potassium addition on microbial carbon use efficiency - Chenyang Zhang; Liyang Sun; Yichao Rui; Yue Li; Yiqi Luo; Minggang Xu; Andong Cai (Global Change Biology, 2023)

Diversity of Fusarium community assembly shapes mycotoxin accumulation of diseased wheat heads - Qiang Wang; Rui Song; Sanhong Fan; Jeffrey J. Coleman; Xiangming Xu; Xiaoping Hu (Molecular Ecology, 2023)
Fusarium head blight (FHB) is a major disease worldwide on cultivated cereals, caused by several Fusarium species. FHB can cause not only yield reduction but also accumulation of mycotoxins in the grain contaminating the food supply. Much of the earlier research has focused on Fusarium pathogenesis, conditions required for disease development and toxin accumulation, and FHB management. However, the Fusarium community composition within the micro‐habitat of a single diseased wheat head in the field has had limited investigation. Similarly, the relationship between the Fusarium community structure and mycotoxin accumulation within diseased heads remains unclear. In the present study, we investigated the Fusarium community in diseased heads sampled from different geographical sites in China. Several sites in Shandong province formed a transitional region which contained highly variable profiles of Fusarium OTUs, where a single diseased head could contain more than 10 Fusarium OTUs. Mycotoxin accumulation was independent of geographical properties, however, deoxynivalenol, 15‐acetyldeoxynivalenol and zearalenone concentrations showed a significant negative correlation with Fusarium diversity on diseased heads while a significant positive correlation between nivalenol concentration and Fusarium diversity was observed. Taken together, the Fusarium OTU diversity within diseased heads in the field significantly influences mycotoxin accumulation, providing an important point to consider in FHB disease management and mycotoxin research.

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Species of fast bulk‐soil nutrient cycling have lower rhizosphere effects: A nutrient spectrum of rhizosphere effects - Lijuan Sun; Yuki Tsujii; Tianle Xu; Mengguang Han; Rui Li; Yunfeng Han; Dayong Gan; Biao Zhu (Ecology, 2023)
Tree roots not only acquire readily‐usable soil nutrients but also affect microbial decomposition and manipulate nutrient availability in their surrounding soils, that is, rhizosphere effects (REs). Thus, REs challenge the basic understanding of how plants adapt to the environment and co‐exist with other species. Yet, how REs vary among species in response to species‐specific bulk soil nutrient cycling is not well‐known. Here, we studied how plant‐controlled microbial decomposition activities in rhizosphere soils respond to those in their corresponding bulk soils and whether these relations depend on species‐specific nutrient cycling in the bulk soils. We targeted 55 woody species of different clades and mycorrhizal types in three contrasting biomes, namely a temperate forest, a subtropical forest, and a tropical forest. We found that microbial decomposition activities in rhizosphere soils responded linearly to those in their corresponding bulk soils at the species level. Thereafter, we found that REs (parameters in rhizosphere soils minus those in corresponding bulk soils) of microbial decomposition activities had negative linear correlations with microbial decomposition activities in corresponding bulk soils. A multiple factor analysis revealed that soil organic carbon, total nitrogen, and soil water content favored bulk soil decomposition activities in all three biomes, showing that the magnitude of REs varied along a fast‐slow nutrient cycling spectrum in bulk soils. The species of fast nutrient cycling in their bulk soils tended to have smaller or even negative REs. Therefore, woody plants commonly utilize both positive and negative REs as a nutrient‐acquisition strategy. Based on the trade‐offs between REs and other nutrient‐acquisition strategies, we proposed a push and pull conceptual model which can bring plant nutrient‐acquisition cost and plant carbon economics spectrum together in the future. This model will facilitate not only the carbon and nutrient cycling but also the mechanisms of species co‐existence in forest ecosystems.

Will climate change cause the global peatland to expand or contract? Evidence from the habitat shift pattern of Sphagnum mosses - Xiao‐Ying Ma; Hao Xu; Zi‐Yin Cao; Lei Shu; Rui‐Liang Zhu (Global Change Biology, 2022)
Peatlands play a crucial role in the global carbon cycle. Sphagnum mosses (peat mosses) are considered to be the peatland ecosystem engineers and contribute to the carbon accumulation in the peatland ecosystems. As cold‐adapted species, the dominance of Sphagnum mosses in peatlands will be threatened by climate warming. The response of Sphagnum mosses to climate change is closely related to the future trajectory of carbon fluxes in peatlands. However, the impact of climate change on the habitat suitability of Sphagnum mosses on a global scale is poorly understood. To predict the potential impact of climate change on the global distribution of Sphagnum mosses, we used the MaxEnt model to predict the potential geographic distribution of six Sphagnum species that dominate peatlands in the future (2050 and 2070) under two greenhouse gas emission scenarios (SSP1‐2.6 and SSP5‐8.5). The results show that the mean temperature of the coldest quarter, precipitation of the driest month, and topsoil calcium carbonate are the main factors affecting the habitat availability of Sphagnum mosses. As the climate warms, Sphagnum mosses tend to migrate northward. The suitable habitat and abundance of Sphagnum mosses increase extensively in the high‐latitude boreal peatland (north of 50°N) and decrease on a large scale beyond the high‐latitude boreal peatland. The southern edge of boreal peatlands would experience the greatest decline in the suitable habitat and richness of Sphagnum mosses with the temperature rising and would be a risk area for the transition from carbon sink to carbon source. The spatial–temporal pattern changes of Sphagnum mosses simulated in this study provide a reference for the development of management and conservation strategies for Sphagnum bogs.

Nitrogen repression of deoxynivalenol biosynthesis is mediated by Mep2 ammonium permease in Fusarium graminearum - Yuting Hu; Rui Hou; Zeyi Wang; Weiwei Zhang; Jin‐Rong Xu (Environmental Microbiology, 2022)
Fusarium graminearum is an important wheat pathogen and a producer of deoxynivalenol (DON). Biosynthesis of DON is suppressed by ammonium and induced by arginine and polyamines. To better understand ammonium repression of DON biosynthesis, in this study, we functionally characterized three ammonium permease ( MEP ) genes in F. graminearum . All the mep deletion mutants were normal in growth on V8 agar. Whereas deletion of MEP1 had no detectable phenotypes, the mep2 and mep3 mutants had defects in hyphal growth under ammonium limiting conditions and infection of wheat heads, with the latter having less severe defects. Deletion of MEP2 but not MEP3 affected nitrogen repression of DON biosynthesis and genes involved in nitrate metabolism. The mep2 mep3 double mutant had more severe defects in nitrogen repression than the mep2 mutant and was defective in ascospore releasing. Mutant alleles of MEP2 with truncated C‐terminal cytoplasmic tail (CT) failed to complement the mep2 mutant. Expression of a dominant active allele of RAS2 partially rescued the defects of mep2 in nitrogen repression. Taken together, these results suggest that Mep2 acts as the major sensor of ammonium availability in F. graminearum and its CT region functions in nitrogen repression via RAS2 and downstream signalling pathways.

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Epigallocatechin‐3‐gallate inhibits replication of white spot syndrome virus in the freshwater crayfish Procambarus clarkii - Yitong Zhang; Jinxuan Wen; Yao Xu; Hao Wang; Liqun Lu; Rui Song; Jixing Zou (Journal of Fish Diseases, 2022)
The freshwater crayfish Procambarus clarkii is native to North America and Mexico, and it was introduced to China in 1929. The production and consumption of P. clarkii in China are the highest worldwide, reaching 208.96 million tons in 2020. The white spot syndrome virus (WSSV) is a major pathogen that affects shrimp, crayfish, crabs and lobsters, and it has caused widespread loss to the P. clarkii industry. Epigallocatechin‐3‐gallate (EGCG), a small‐molecule compound, has a multitude of biological functions and the ability to bind to the 37 kDa/67 kDa laminin receptor ( LamR ). EGCG has potential antiviral effects against WSSV. In this study, we evaluated the potential anti‐WSSV applications of EGCG in P. clarkii . We demonstrated that various concentrations (10 μg/g·bw, 20 μg/g·bw and 40 μg/g·bw) of EGCG can suppress WSSV infection in P. clarkii . Histopathological examination revealed no characteristic pathological changes due to EGCG administration in P. clarkii tissues. Furthermore, pharmacokinetics studies of EGCG in P. clarkii revealed its rapid absorption (T max = 2 h), and the peak concentrations of EGCG were 73.78 µg/g in the liver and 24.87 µg/g in the muscle. Our results indicate the high potential applications of EGCG against WSSV in P. clarkii .

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Vertical influence of temperature and precipitation on snow cover variability in the Yarlung Zangbo River basin, China - Chunguang Ban; Zongxue Xu; Depeng Zuo; Xiaowan Liu; Rui Zhang; Jing Wang (International Journal of Climatology, 2021)
Seasonal snow cover in mountainous areas is a key source of water for downstream regions. The snow cover area (SCA) in the Northern Hemisphere has significantly decreased during the past decades in response to global warming. Therefore, it is necessary to investigate the primary factors controlling the spatiotemporal variabilities in the SCA in high altitude regions. In this study, based on remote sensing data of SCA, temperature, and precipitation in the Yarlung Zangbo River basin, Pearson's correlation analysis was used to identify the relative importance of temperature and precipitation on the SCA variability with altitude. The results showed that temperature played a more dominant role for the SCA than precipitation at all elevation during the period 2001–2017; three threshold altitudes at high, moderate, and low elevation were identified, and these threshold altitudes are dynamic and vary with time; the threshold altitude at high elevation was 5,925 ± 125 m, below which temperature (precipitation) was negatively (positively) correlated and above which temperature (precipitation) was positively (negatively) correlated with the SCA; the threshold altitude at moderate elevation was 3,200 ± 300 m, below which temperature (precipitation) was positively (negatively) correlated and above which temperature (precipitation) was negatively (positively) correlated with the SCA; the threshold altitude in low elevation regions was 2,100 ± 200 m. This study sheds light on the dominant climatic control factors on the variability in SCA in high altitude regions. These results have major implications for SCA and water resources availability under future climate change.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Elevated atmospheric CO 2 reduces yield‐scaled N 2 O fluxes from subtropical rice systems: Six site‐years field experiments - Zhisheng Yao; Rui Wang; Xunhua Zheng; Baoling Mei; Zaixing Zhou; Baohua Xie; Haibo Dong; Chunyan Liu; Shenghui Han; Zhongjun Xu; Klaus Butterbach‐Bahl; Jianguo Zhu (Global Change Biology, 2021)
Increasing levels of atmospheric CO 2 are expected to enhance crop yields and alter soil greenhouse gas fluxes from rice paddies. While elevated CO 2 ( ) effects on CH 4 emissions from rice paddies have been studied in some detail, little is known how might affect N 2 O fluxes or yield‐scaled emissions. Here, we report on a multi‐site, multi‐year in‐situ FACE (free‐air CO 2 enrichment) study, aiming to determine N 2 O fluxes and crop yields from Chinese subtropical rice systems as affected by . In this study, we tested various N fertilization and residue addition treatments, with rice being grown under either (+200 μmol/mol) or ambient control. Across the six site‐years, rice straw and grain yields under were increased by 9%–40% for treatments fertilized with ≥150 kg N/ha, while seasonal N 2 O emissions were decreased by 23%–73%. Consequently, yield‐scaled N 2 O emissions were significantly lower under . For treatments receiving insufficient fertilization (≤125 kg N/ha), however, no significant effects on N 2 O emissions were observed. The mitigating effect of upon N 2 O emissions is closely associated with plant N uptake and a reduction of soil N availability. Nevertheless, increases in yield‐scaled N 2 O emissions with increasing N surplus suggests that N surplus is a useful indicator for assessing N 2 O emissions from rice paddies. Our findings indicate that with rising atmospheric CO 2 soil N 2 O emissions from rice paddies will decrease, given that the farmers’ N fertilization is usually sufficient for crop growth. The expected decrease in N 2 O emissions was calculated to compensate 24% of the simultaneously observed increase in CH 4 emissions under . This shows that for an agronomic and environmental assessment of effects on rice systems, not only CH 4 emissions, but also N 2 O fluxes and yield‐scaled emissions need to be considered for identifying most climate‐friendly and economically viable options for future rice production.

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

Novel phage–host interactions and evolution as revealed by a cyanomyovirus isolated from an estuarine environment - Yongle Xu; Rui Zhang; Nannan Wang; Lanlan Cai; Yigang Tong; Qiang Sun; Feng Chen; Nianzhi Jiao (Environmental Microbiology, 2018)
Summary Cyanophages are thought to affect the community structure, population dynamics, metabolic activity and evolution of picocyanobacteria and to impact the biogeochemical cycling in aquatic ecosystems. Here, we report an estuarine Synechococcus phage, S‐CBWM1, which represents a novel viral lineage and exhibits interesting genetic features related to phage–host interactions and evolution. S‐CBWM1 encapsidates four virion‐associated proteins related to cellular metabolic regulation. Several novel auxiliary metabolic genes related to multidrug efflux, cell wall and capsule synthesis or modifications were also identified. In addition, the presence of the largest number of tRNA genes hitherto found in a phage genome may contribute to the translation efficiency of unique genes. These genomic and proteomic features of S‐CBWM1 suggested phage–host interactions involved in adaptation to eutrophic estuarine environments. Phylogenetic and metagenomic analysis of the pol γ gene in the S‐CBWM1 genome provided new insights into the evolutionary path of mitochondrial DNA polymerase gamma. The S‐CBWM1 psbA contains two group I introns, representing the first instance of multiple introns within psbA from phage. The isolation of S‐CBWM1 reveals that estuarine ecosystems contain evolutionarily novel cyanophages that drive unique phage–host interactions.

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Effects of warming and grazing on soil N availability, species composition, and ANPP in an alpine meadow - Shiping Wang; Jichuang Duan; Guangping Xu; Yanfen Wang; Zhenhua Zhang; Yichao Rui; Caiyun Luo; Burenbayin Xu; Xiaoxue Zhu; Xiaofeng Chang; Xiaoyong Cui; Haishan Niu; et al. (Ecology, 2012)
Uncertainty about the effects of warming and grazing on soil nitrogen (N) availability, species composition, and aboveground net primary production (ANPP) limits our ability to predict how global carbon sequestration will vary under future warming with grazing in alpine regions. Through a controlled asymmetrical warming (1.2/1.7°C during daytime/nighttime) with a grazing experiment from 2006 to 2010 in an alpine meadow, we found that warming alone and moderate grazing did not significantly affect soil net N mineralization. Although plant species richness significantly decreased by 10% due to warming after 2008, we caution that this may be due to the transient occurrence or disappearance of some rare plant species in all treatments. Warming significantly increased graminoid cover, except in 2009, and legume cover after 2008, but reduced non‐legume forb cover in the community. Grazing significantly decreased cover of graminoids and legumes before 2009 but increased forb cover in 2010. Warming significantly increased ANPP regardless of grazing, whereas grazing reduced the response of ANPP to warming. N addition did not affect ANPP in both warming and grazing treatments. Our findings suggest that soil N availability does not determine ANPP under simulated warming and that heavy grazing rather than warming causes degradation of the alpine meadows.